STRATÉGIES DE RÉSILIENCE DU SYSTÈME SANITAIRE IVOIRIEN EN SITUATION DE CRISE ARMÉE : LE CAS DE LA VILLE DE BOUAKÉ. - Brahima, Coulibaly (European Scientific Journal, ESJ, 2015)
The military crisis experienced by Côte d’Ivoire has weakened the health system, especially in the area occupied by the rebellion. Our goal here is to show impact strength strategies developed by health actors in Bouaké during the period from 2002 to 2007. A semi-structured interview guide was addressed to representatives of official structures, international and national NGOs which have intervened in the field of health during this period. An interview guide was also addressed to people who have had health problems during the period indicated. These tools have been reinforced by the documentation. It arises from the investigations that facing the failure of the medical system of the Ivory Coast, one attended the emergence of new actors who are ONG international. While offering services of care, they also reinforced the capacities of the local structures (official and ONG main roads) in average equipment, equipment, financial, drugs, formations, etc. By relaying the official structures these new actors placed the emphasis on collaboration, solidarity, the recruitment of staff, the formation, the selection of the activities, the extrinsic motivation, the installation of a mobile private clinic, the orientation of the patients towards the governmental area and the use of the air routes to meet the medical needs for the populations. As for the populations, they had the choice between the recourse to the offers of care of the new actors, self medication and the recourse to the tradipraticians of health. These actions fall under the process of impact strength expressible as regards protection, prevention, promotion and transformation.